2011
DOI: 10.1128/iai.05290-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an ATPase, MsmK, Which Energizes Multiple Carbohydrate ABC Transporters in Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is the leading cause of community-acquired pneumonia and results in over 1 million deaths each year worldwide. Asymptomatic colonization of the airway precedes disease, and acquisition of carbohydrates from the host environment is necessary for bacterial survival. We previously demonstrated that S. pneumoniae cleaves sialic acid from human glycoconjugates to be used as a carbohydrate source. The satABC genes are required for growth and import of sialic acid. The satABC genes are predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 43 publications
6
101
2
Order By: Relevance
“…It had previously been suggested that import by this transporter was not energized by MsmK because an msmK mutant had no growth defect on sucrose (6,21). We believe that growth on sucrose is primarily via the PTS ScrT, which is ATPase independent, and therefore, loss of the ATPase does not affect growth under these conditions.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…It had previously been suggested that import by this transporter was not energized by MsmK because an msmK mutant had no growth defect on sucrose (6,21). We believe that growth on sucrose is primarily via the PTS ScrT, which is ATPase independent, and therefore, loss of the ATPase does not affect growth under these conditions.…”
Section: Discussionmentioning
confidence: 85%
“…We also demonstrate that mutation of msmK does not further reduce the growth of the scrT mutant on GF2 (data not shown). As msmK has been demonstrated to energize all pneumococcal CUT1 family trans- porters of known function (21), these data suggest that residual transport is due to the PTS. It was previously reported that FusH (SusH) can compensate for the loss of ScrH during growth on sucrose (3).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Addition of 100 M MnCl 2 , a toxic concentration for L. interrogans (Fig. 2) (48)(49)(50), although to our knowledge not with both import and export systems. Alternatively, the LEPBIa2866 or LIC12079 ATPase could serve in a non-transport-related process that allows utilization of Mn 2ϩ .…”
Section: Discussionmentioning
confidence: 99%